SYSTEM TRANSACTION ALERT UNTUK MENGURANGI KREDIT MACET YANG DITIMBULKAN DARI KEJAHATAN ATAS PENYALAHGUNAAN KARTU KREDIT DI INDONESIA - YUDHA PRABOWO, RANGGA Yudha (Jurnal Akuntansi AKUNESA, 2013)
This article aims to provide an argument about the transaction alert system that willbe implemented in Indonesia. At this time, transaction alert system is believed as a solution toprevent the crime of misuse of credit cards. The purpose of this study is to examine whetherthe transaction alert system can be implemented in Indonesia. This study is a comparativestudy toward countries that have implemented transaction alert system. It is compared toUnited States, India, and Malaysia. The results of a comparative study shows that theimplementation of the transaction alert in each country are not much different. The thing hasdone in order to go ahead transaction alert in Indonesia is the awareness of customers toplay an active role in the transaction alert and a cooperative relation between bank andtelephone provider. Key words: credit card crime, transaction alert, bank, customers